2014
DOI: 10.1016/j.procs.2014.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Usability on the Edge: The Implementation of u:cris at the University of Vienna

Abstract: Delivered at the CRIS2014 Conference in Rome; published in Procedia Computer Science 33 (Jul 2014).Contains conference paper (7 pages) and presentation (24 slides).In 2011, the top management of the University of Vienna made a fundamental (and possibly trend-setting) decision to replace the old research information system with a contemporary vendor system. This paper highlights the reasons behind the decision and illustrates the implementation process, which is not only a challenge from a technical point of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…Although the quality of research information in general has been widely discussed, and data quality has been a major issue in many CRIS implementation projects (see, e.g., [30][31][32][33][34]), issues related to the migration of legacy publication data have remained surprisingly overlooked. Bevan and Harrington [35] described lessons learned from implementing a CRIS platform at Cranfield University, which was accomplished within a year using Converis.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the quality of research information in general has been widely discussed, and data quality has been a major issue in many CRIS implementation projects (see, e.g., [30][31][32][33][34]), issues related to the migration of legacy publication data have remained surprisingly overlooked. Bevan and Harrington [35] described lessons learned from implementing a CRIS platform at Cranfield University, which was accomplished within a year using Converis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Buchmayer et al [31] reported a Pure implementation at the University of Vienna. Although not focusing on data quality, the authors noted that the implementation of master data synchronization involved a higher-than-expected workload, and the migration of existing data led to problems that had not been considered before.…”
Section: Literature Reviewmentioning
confidence: 99%